Waterpipe Tobacco Smoke Nicotine Mediates Resilience to Chronic Stress by Activating BDNF Signaling - Khalifeh, Mohamad Rabieh (2020)
The purpose of this study was to investigate how nicotine in the context of waterpipe tobacco smoking (WTS) affects depression and anxiety-like behaviors associated with chronic social defeat stress (CSDS) in a male C57BL/6J animal model. The mice were exposed to WTS or received intraperitoneal injections of nicotine for thirty days, before being subjected to CSDS for ten days. During CSDS, mice were exposed to WTS or received nicotine injections. The social interaction and open-field tests were used to classify animals as resilient or susceptible to stress and to evaluate their anxiety-like behavior and social interaction. Mice post behavioral testing, were further exposed to WTS/nicotine for ten days, and their behavior was reassessed. The involvement of brain-derived neurotrophic factor signaling in the nicotine-mediated effects was assessed with the tropomyosin receptor kinase B (TRKB) inhibitor, ANA-12. The reported results indicated that WTS promoted resilience to stress and rescued social avoidance in the used mice model. Even though initially, WTS decreased anxiety-like behaviors it was found that prolonged exposure after the completion of CSDS significantly induced anxiety-like behaviors. Finally, we showed that nicotine mediates the effects of WTS only on resilience to stress by increasing BDNF and TRKB levels and signaling. Our results suggested that the pathways mediating resilience to stress and anxiety are distinct and that nicotine mediates the effects of WTS on social behavior, but not anxiety, by activating BDNF signaling.